Pengaruh Literasi Keuangan Pelaku Usaha Kecil Terhadap Kinerja Keuangan Usaha di Kota Makassar - Iqra Aiman Mufid; Romansyah Sahabuddin; Anwar; Burhanuddin; Zainal Ruma (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2023)
This study aims to determine the effect of financial literacy of small business actors on the financial performance of businesses in the city of Makassar. The population in this study are all small businesses recorded at the Makassar City Cooperatives and UKM Office in 2022, namely 136 businesses. The type of data used in this study is quantitative data obtained from questionnaires distributed to 58 samples related to the problem being studied. Funds were analyzed using a simple regression analysis method with the help of SPSS data processing to prove the hypothesis. The results of this study indicate that financial literacy has a positive and significant effect on business financial performance. The better the level of financial literacy of business actors, the better the performance will be.